Amadori and Heyns rearrangement products of bioactive peptides as potential new ligands of galectin-3 - Jakas, Andreja; Ayyalasomayajula, Ramya; Cudic, Mare (Carbohydrate research, 2024)
Non-enzymatic cascade reactions between amines and reducing sugars are known as Maillard reaction. The late phase of these reactions consists of advanced glycation end products (AGEs), which have been implicated in the pathogenesis of numerous human diseases. Recent evidence suggests that galectin-3 acts as a receptor for AGEs and some early products of the Maillard reaction. The early phase of the Maillard reaction, which consists of 1-amino-1-deoxyketoses (Amadori compounds) and 2-amino-2-deoxyaldoses (Heyns compounds), was the subject of our study. The binding interactions between galectin-3 and the Amadori and Heyns compounds of leucine-enkephalin (YGGFL), leucine-enkephalin methyl ester (YGGFL-OMe), truncated enkephalin (YGG and Y) and tetrapeptide (LSKL) were measured using the AlphaScreen competitive binding assay. The affinity of galectin-3 for Amadori and Heyns compounds depends on both the sugar moiety and the amino acid sequence of the model compounds. The best results were obtained with Leu-enkephalin derivatives of Amadori (IC50 = 6.06 μm) and Heyns (IC50 = 8.6 μm) compound, respectively. [Display omitted] •The interactions between Amadori and Heyns compounds of Leu-enkephalin and the tetrapeptide Leu-Ser-Lys-Leu with galectin-3 were investigated.•The AlphaScreen competitive binding assay was used to study the interactions of Amadori and Heyns compounds with galectin-3.•The Heyns compounds showed a higher affinity for galectin-3 compared to Amadori compounds.•The lack of the aromatic residues within the peptide sequence, showed a significantly lower affinity for galectin-3.